Kinematics and Workspace Analysis of a New Type of 3-DOF Redundant Parallel Mechanism - Xiaoru Li; Juan Huang; Xinghui Li (Jixie chuandong, 2019)
Due to higher stiffness, better dynamics performance, etc., the redundantly driven parallel mechanisms are increasingly used in various industries. A 3-DOF redundant parallel mechanism with a double-slider structure is proposed. Based on the direct position solution and inverse position solution, the kinematics equation of the mechanism is deduced separately, and the kinematics simulation are carried out by combining the inverse solution equation with MATLAB to draw the drive displacement and speed. Combining kinematics analysis results and direct position solution equations to analyze the workspace of the mechanism, and drawing the three-dimensional workspace of the mechanism. The results of kinematics and workspace show that the mechanism runs smoothly in the workspace, without sudden change in speed, displacement, etc., and the workspace has good symmetry about XOZ. The research results also provide the foundation for the practical redundant application of this configuration redundant parallel mechanism.